Respuesta :
[tex] \bf slope = m = \cfrac{rise}{run} \implies
\cfrac{ f(x_2) - f(x_1)}{ x_2 - x_1}\impliedby
\begin{array}{llll}
average~rate\\
of~change
\end{array}\\\\
-------------------------------\\\\
f(t)= 3t^2 \qquad
\begin{cases}
t_1=1\\
t_2=1.001
\end{cases}\implies \cfrac{f(1.001)-f(1)}{1.001-1}
\\\\\\
\cfrac{3(1.001)^2~~-~~3(1)^2}{0.001}\implies \cfrac{3.006003~-~3}{0.001}
\\\\\\
\cfrac{0.006003}{0.001}\implies 6.003 [/tex]
Answer:
Since, for a function f(x),
[tex]\text{Average rate of change between }x_1\text{ and }x_2=\frac{f(x_2)-f(x_1)}{x_2-x_1}[/tex]
Given function,
[tex]f(t)=3t^2[/tex]
Thus,
(a) the average rate of change of f(t) between t=1 and t=1.001
[tex]=\frac{f(1.001)-f(1)}{1.001-1}[/tex]
[tex]=\frac{3(1.001)^2-3(1)^2}{0.001}[/tex]
[tex]=6.003[/tex]
(b) the average rate of change of f(t) between t=2 and t=2.001
[tex]=\frac{f(2.001)-f(2)}{2.001-2}[/tex]
[tex]=\frac{3(2.001)^2-3(2)^2}{0.001}[/tex]
[tex]=12.003[/tex]
(c) the average rate of change of f(t) between t=3 and t=3.001
[tex]=\frac{f(3.001)-f(3)}{3.001-3}[/tex]
[tex]=\frac{3(3.001)^2-3(3)^2}{0.001}[/tex]
[tex]=18.003[/tex]
(d) the average rate of change of f(t) between t=4 and t=4.001
[tex]=\frac{f(4.001)-f(4)}{4.001-4}[/tex]
[tex]=\frac{3(4.001)^2-3(4)^2}{0.001}[/tex]
[tex]=24.003[/tex]
[tex]=6.003[/tex]